Postal History of the Falkland Islands Dependencies - Bagshawe, Richard W. (Polar Record, 1947)
The Antartic continent has been in the limelight during the past year, and it is well known that several countries are claiming parts of the area, which unfortunately overlap. Possessions belonging to Great Britain, but at present disputed, are all islands and territories lying between longitudes 20°and 50° W., south of latitudes 58° S. The islands enclosed by these boundaries are Dependencies of the Falkland Islands consisting of many islands and part the Antartic Continent. South Georgia, the South Orkney Islands, Graham Land, the South Shetland Islands, the South Sandwich Islands, Alexander I Land and part of Coats Land lie within this area, which amounts in all to about three million square miles, and the territories, portions of which are as yet unexplored, extend down to the South Pole. Great Britain permanently occupies the Dependencies, carrying on a whaling industry and scientific research. In addition the Argentine Government has a meteorological station on Laurie Island in the South Orkneys. This was established in 1904 at the request of Dr W. S. Bruce, leader of the Scottish National Antarctic Expedition, who had built the station two years earlier. Since 1904 it has been continually manned by meteorologists sent out each year from Argentina. The original party had a post office, the first to appear in Antarctica. This and the more recent ones set up under British administration are marked on the accompanying map. Owing to the impermanence of the population of this part of the world they are naturally not all open continuously.